COVID-19 and domestic violence: impact to mental health. Issue 3 (12th July 2021) - Ali, Parveen; Rogers, Michaela; Heward-Belle, Susan
Abstract : Purpose: This paper aims to explore the mental health impact of domestic violence and abuse within the context of the global pandemic. This paper will explore factors contributing to rising rates of violence and mental health problems exacerbated by stressors related to the global pandemic, including public health measures implemented to prevent the spread of coronovirus disease (COVID-19). It will also explore what can be learnt from the current pandemic situation to prevent domestic violence and abuse in future emergency situations and pandemics and will provide suggestions, for policy, practice and future research. Design/methodology/approach: This paper is informed by discussion between authors as experts in the field, their reflection on the current situation and review of available literature. Synthesising information from best practice guidance across the global literature, this paper proposes a best practice framework using an ecological approach to address intimate partner violence in times of pandemic, crisis or natural disaster. Findings: This paper aimed to explore the mental health impact of domestic violence and abuse within the context of the global pandemic. Originality/value: This paper provides an analysis of available literature and explains impact of COVID-19 on domestic violence and abuse.